Organizing state and local health departments for public health preparedness - Wasserman, Jeffrey; Jacobson, Peter D.; Lurie, Nicole; Nelson, Christopher; Ricci, Karen; Shea, Molly V.; Zazzali, James; Nelson, Martha I. (Technical report (Rand Corporation), 2006)
Improving the ability to respond to bioterrorism and other emergencies is an important challenge facing the U.S. public health system. Despite having a knowledgeable workforce, practice and experience, capacity, and partnerships with other responders in the community, the system₂s ability to respond may depend largely on its structure. This study examines a key question: Are state and local public health agencies related to one another in a way that facilitates emergency response? Specific objectives of this study are to explain the factors influencing the particular ways in which state and local public health systems are organized, how the various types of relationships that exist between state and local public health departments have been arrived at, and, most important, the consequences of such structures and relationships for emergency preparedness. We also examine alternative structures from several different types of service industries (public education, banking, the welfare system, and port authorities). Finally, we recommend concrete strategies to improve public health preparedness. This report will be of interest to policymakers and to public health professionals at the state and local levels who are involved in bioterrorism response and emergency preparedness, as well as to other agencies involved in emergency response.